The Use of Isohemagglutinating Serums and Phytagglutinins in Forensic Medical Examination (Eurasian Journal of Research, Development and Innovation, 2023)
The authors consider a comparative study of α and β sera and phytagglutinins under the influence of high temperature.The intensity of agglutination of the alpha and β serum was the same both when exposed to temperature for 30 minutes and at 8 hours of exposure at 30 and 200C, their titer was 1:64.Under conditions of 370 and 480C, the agglutination ability of alpha and β serum increases, their titer is 1:128.The activity of extracts from Phaseolus vulgaris Savi seeds increases with a temperature change from 30 to 480C and their titer is 1:256. The activity of extracts from Nimrang grape seeds does not increase with a temperature change from 30 to 480C and their titer is 1:64